Relationship Between Leisure Constraints and Residential School Students’ Participation in Recreational Sport Activities - A. Rahim, Sakhiyyah (2004)
The purpose of this study is to investigate the relationship that exists among these two variables: leisure constraint, and students’ participation in recreational sport activities in selected fully residential schools in Johor. The sample selected comprised of 217 respondents in three fully residential schools in the state of Johor. A pilot test was conducted to obtain the reliability of the instruments used. The Cronbach Alpha showed the overall reliability of above .65. The data collected were coded and analyzed using descriptive and inferential statistics. Based on the analysis done, the following findings were discovered. First, the result indicated that leisure constraint was not affected by gender differences. Male and female students experienced approximately the same amount of constraint. Second, male and female respondents reported differences in the intensity of leisure dimensions constraint experienced. Interpersonal constraint was found to be significantly different in the intensity as compared to the other two leisure constraint dimensions. Third, there was a significant linear negative relationship between leisure constraint and student’s participation (r= -.258, p= .0001, p< .05). This suggested that an increase in the intensity of constraint experienced would likely be followed by a decrease in students’ participation. Fourth, analysis conducted on the leisure constraint dimensions revealed that of the three dimensions, intrapersonal was noted as the most influential (p= .0001, p< .05). In conclusion, the findings confirmed that leisure constraint and students’ participation were interconnected. Each one of it had an effect on another.